2004
DOI: 10.1243/0954411041932782
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of poly-L-lactide. Part 1: in vitro and in vivo physiological temperature degradation

Abstract: Poly-L-lactide (PLLA) is one of the most significant members of a group of polymers regarded as bioresorbable. The degradation of PLLA proceeds through hydrolysis of the ester linkage in the polymer's backbone and is influenced by the polymer's initial molecular weight and degree of crystallinity. To evaluate its degradation PLLA pellets were processed by compression moulding into tensile test specimens and by extrusion into 2 mm diameter lengths of rod, prior to being sterilized by ethylene oxide gas (EtO) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
117
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 160 publications
(132 citation statements)
references
References 47 publications
15
117
0
Order By: Relevance
“…Compression results on PGSm conduits showed an average Young's modulus of 3.2 MPa, similar to that of the native nerve (0.45 MPa) [44]. This similarity is further understood when compared with polycaprolactone (PCL), poly-L-lactide (PLLA) and poly(3-hydroxybutyrate) (P3HB), materials widely researched for peripheral nerve repair, with reported modulus values of 400 MPa, 668.4 MPa, 1160 MPa, respectively, far stiffer than that of the native nerve [25,[45][46][47][48]. Suture retention mechanical tests found PGSm conduits to have an average suture retention strength of 12.3 MPa, similar to the value reported for clinically used poly(tetrafluoroethylene) (as Gore-Tex vascular grafts), 23 MPa [49][50][51].…”
Section: Tablementioning
confidence: 62%
“…Compression results on PGSm conduits showed an average Young's modulus of 3.2 MPa, similar to that of the native nerve (0.45 MPa) [44]. This similarity is further understood when compared with polycaprolactone (PCL), poly-L-lactide (PLLA) and poly(3-hydroxybutyrate) (P3HB), materials widely researched for peripheral nerve repair, with reported modulus values of 400 MPa, 668.4 MPa, 1160 MPa, respectively, far stiffer than that of the native nerve [25,[45][46][47][48]. Suture retention mechanical tests found PGSm conduits to have an average suture retention strength of 12.3 MPa, similar to the value reported for clinically used poly(tetrafluoroethylene) (as Gore-Tex vascular grafts), 23 MPa [49][50][51].…”
Section: Tablementioning
confidence: 62%
“…Assuming that the concentrations of ester bonds and water are approximately constant throughout the degradation process and that the concentration of carboxylic acid end groups is inversely proportional to the number-average molecular weight (Mn) of the polymer (ie, [COOH]檄1/Mn), Weir and coworkers 57,58 showed that…”
Section: Bioresorption Process Of Pllamentioning
confidence: 99%
“…In accordance with ISO15814, samples were placed in glass vials containing 15 ml of phosphate buffered saline (PBS, pH 7.4). For accelerated degradation, a higher temperature of 70 C was used [18,19]. At defined time points, samples were removed from the PBS, filtered through Grade 1 filter paper and rinsed with distilled water.…”
Section: Accelerated Degradationmentioning
confidence: 99%